Transformasi Ekonomi di Wilayah Pesisir: Mengoptimalkan Peran Strategis Pelabuhan Laut dalam Meningkatkan Konektivitas, Produktivitas, Keberlanjutan, serta Peluang, Tantangan, dan Strategi di Provinsi Banten - Aziz, Abdul; Alifah, Atina; Nulhakim, Lucky Lukman; Ma’ruf, Ma’ruf (Universitas Pahlawan Tuanku Tambusai, 2025)
Seaports play an important role in driving the economic transformation of coastal areas. This article examines how seaport infrastructure and activities can increase local economic productivity, attract investment, and drive growth in other sectors such as fisheries, tourism, and transportation. Focusing on Banten Province, the study uses SWOT analysis to identify opportunities and challenges faced in developing the maritime sector. The results show that the presence of seaports contributes significantly to increasing Gross Regional Domestic Product (GRDP), creating jobs, and strengthening inter-island connectivity, despite challenges such as environmental damage, overfishing, and policy misalignment.